Pelatihan Penyusunan Laporan Keuangan BUMDes Momposa Angu Desa Biak Kec. Luwuk Utara Kab. Banggai - Siswadi Sululing; Yanti Mutalib (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2022)
The purpose of this activity is to improve the ability and skills of BUMDes management, especially the Treasurer in recording financial transactions so that they can prepare BUMDes financial reports. This service activity is carried out using the BUMDes accounting training method and the preparation of BUMDes financial reports. The material provided in this training consists of theoretical material on accounting science to record all BUMDes financial transactions, namely income, cost, asset, debt and capital transactions, while practical material is the preparation of BUMDes financial reports. In this practice, mentoring is also carried out with the aim of making it easier for participants to understand so that they can prepare BUMDes financial reports correctly and accountably in the future. To measure the level of success, it is done by holding a pre-test and post-test, the value of the two tests is divided by 2, so that the average value is obtained. At a minimum, training participants must get a score of 60. The results achieved are able to improve the ability and skills in recording financial transactions so that they are able to prepare BUMDes financial reports correctly, and provide benefits to the performance of BUMDes management.